Null Mutation of the Nicotinamide Adenine Dinucleotide Phosphate–Oxidase Subunit p67phox Protects the Dahl-S Rat From Salt-Induced Reductions in Medullary Blood Flow and Glomerular Filtration Rate. Issue 3 (March 2015) - Evans, Louise C.; Ryan, Robert P.; Broadway, Elizabeth; Skelton, Meredith M.; Kurth, Theresa; Cowley, Allen W.
<x xml:space="preserve">Abstract</x> Null mutations in the p67phox subunit of nicotinamide adenine dinucleotide phosphate–oxidase confer protection from salt sensitivity on Dahl salt-sensitive rats. Here, we track the sequential changes in medullary blood flow (MBF), glomerular filtration rate (GFR), urinary protein, and mean arterial pressure in SSp67phox null rats and wild-type littermates during 21 days of 4.0% NaCl high-salt (HS) diet. Optical fibers were implanted in the renal medulla and MBF was measured in conscious rats by laser Doppler flowmetry. Separate groups of rats were prepared with femoral venous catheters and GFR was measured by the transcutaneous assessment of fluorescein isothiocyanate-sinistrin disappearance curves. Mean arterial blood pressure was measured by telemetry. In wild-type rats, HS caused a rapid reduction in MBF, which was significantly lower than control values by HS day-6. Reduced MBF was associated with a progressive increase in mean arterial pressure, averaging 170±5 mm Hg by HS salt day-21. A significant reduction in GFR was evident on day-14 HS, after the onset of hypertension and reduced MBF. In contrast, HS had no significant effect on MBF in SSp67phox null rats and the pressor response to sodium was blunted, averaging 150±3 mm Hg on day-21 HS. GFR was maintained throughout the study and proteinuria was reduced. In summary, when p67phox is not functional in the salt-sensitive rats, HS does not cause reduced MBF and salt-sensitive hypertension is attenuated, and consequently renal injury is reduced and GFR is maintained.